Eye Movement Desensitization and Reprocessing (EMDR) Therapy for Handling Post Traumatic Stress Disorder (PTSD) Respondents - Eka Susanty; Setyono Koesno; Candra Yudhistira; Lulu Lusianti; Suprijanto Suprijanto (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2015)
EMDR therapy is designed to reduce distress related traumatic event. PTSD prevalence is large enough in Indonesia. It was caused by many natural disasters that happened in several area of Indonesia. However, the application of EMDR for reducing PTSD symptoms was still rare. The objective of this study was to examine the intervention of EMDR therapy in handling PTSD respondents and using a one group pretest-posttest design. There were nine PTSD respondents involved during treatment. EMDR treatments were conducted in four repetitive sessions. Each session was completed in 60-90 minutes. Data was taken using PSS (PTSD Symptom Scale) and tested with Wilcoxon statistical analysis. The statistic test showed (Z = - 2.668; p = .05) with Asymp. Sig. =.008. Descriptive data showed that mean scores before and after therapy are 30.88 and 15.77 respectively. This research concluded that EMDR therapy can work to decrease PTSD symptoms.